SPECIALIZED EDUCATIONAL ASSISTANCE AND MEANINGFUL LEARNING: PRACTICES THAT MAKE A DIFFERENCE - de Sousa, Rodger Roberto Alves; Sorrentino, Denise da Silva Rodrigues Guennes (Seven Editora, 2026)
This article addresses the role of Specialized Educational Assistance (SEA) in promoting meaningful learning and the comprehensive development of students with special educational needs. It discusses the pedagogical foundations of SEA, the importance of intentional planning, pedagogical mediation, individualized support, and articulation with regular classrooms, highlighting how these practices foster effective inclusion and the enhancement of students’ potential. The study shows that diversified pedagogical strategies, adapted resources, and assistive technologies are essential tools to meet each student’s singularities, enabling the construction of relevant and lasting knowledge. Process-oriented assessment is presented as central for monitoring progress, adjusting interventions, and ensuring educational objectives are consistently achieved. Furthermore, challenges in daily SEA practice, such as resource limitations, teacher training, and the need for professional collaboration, are discussed alongside opportunities for pedagogical innovation. The article emphasizes that continuous reflection on teaching practices, combined with ongoing professional development, is crucial for the effectiveness of educational actions and the consolidation of quality inclusive education. Therefore, SEA, by integrating planned practices, diversified strategies, and individualized support, proves indispensable for ensuring meaningful learning, promoting equity, and strengthening the comprehensive development of students with special educational needs. DOI: https://doi.org/10.56238/sevened2026.004-001